Serum total and high-density lipoprotein phospholipid levels in a population-based study and relationship to risk of metabolic syndrome and coronary disease - Hergenc, Gulay; Onat, Altan; Sari, Ibrahim; Yazici, Mehmet; Eryonucu, Beyhan; Can, Gunay (SAGE PUBLICATIONS INC, 2008)
The aim of study was to investigate the role of serum total (TPL) and high-density lipoprotein phospholipids (HDL-pl) as a risk factor in coronary heart disease (CHD) and metabolic syndrome (MS). In a random sample, total and HDL-pI were measured in 1088 and 642 adults from Turkey, respectively, who have a high prevalence of MS; this was done with an enzymatic method that measures total phosphatidylcholine, sphingomyelin, and lysophosphatidylcholine. Serum TPL and HDL-pl levels were significantly higher in women (TPL, 2.8 mmol/L; HDL-pl, 1.21 mmol/L) than in men. Strong correlations existed between serum TPL levels and non-HDL cholesterol (HDL-C), triglycerides, apolipoprotein (apo) B, complement C3, and gamma-glutamyltransferase. Non-HDL-C, HDL triglyceride, and apo A-I were strongly correlated with HDL-pl. Linear regression analyses revealed HDL-C, apo B, triglycerides, diabetes, and female gender as independent significant determinants of TPL levels in adults. HDL-C and impaired glucose regulation were sole significant variables, together contributing one-quarter of serum HDL-pl. Individuals with MS or diabetes had significantly higher TPL concentrations. The gender- and age-adjusted odds ratio (OR) of TPL for MS was 1.73 (95% confidence interval, 1.35-2.21), whereas the multiadjusted OR of HDL-pl per 1 SD increment corresponded to a significantly reduced independent MS likelihood by 26% in women (and 18% in the entire group). The multiadjusted OR of HDL-pl for CHD in men and women combined was 0.32 (P =.057) corresponding to a reduced CHD likelihood by 32% per I SD increment of HDL-pl. Plasma TPL levels point to an adverse relationship to MS, whereas their role in CHD risk needs further investigation. HDL-pls, in contrast, mark substantial protection from MS as well as from CHD.
Keywords: phospholipids; population-based study; coronary heart disease; metabolic syndrome; EFFLUX CAPACITY; CHOLESTEROL; HDL; PLASMA; INFLAMMATION; Cardiovascular System & Cardiology